Derivation of resident macrophages and construction of tumor microenvironment in Flk-1-knockout chimeric mice produced via blastocyst complementation - Satoko Ishii; Kazuto Yamazaki; Peng Li; Kenji Kubara; Yuta Ishizuka; Yukina Izumi; Tsutomu Kamisako; Hiroyoshi Ishizaki; Yuichi Ono; Naoaki Mizuno; Hideyuki Sato; Hideki Masaki; et al. (Scientific Reports)
Abstract The tumor microenvironment (TME) is deeply involved in cancer progression and treatment resistance. Although humanized mouse models have been developed by transplanting human cells into immunodeficient mice, they fail to fully reconstitute the TME. Blastocyst complementation using Flk-1 (Vegfr2, Kdr) knockout hosts offers a potential solution. However, the generation of interspecies human–mouse chimeras using blastocyst complementation has not yet been successful. As a foundational step, this study aims to demonstrate that donor-derived TME can be constructed using this method in intraspecies chimeric mice. We generated chimeric mice by injecting Azami-Green (AG)-positive C57BL/6 (B6) mouse-derived embryonic stem cells (ESCs) into ICR Flk-1 knockout embryos. We observed that vascular endothelial cells (VECs), hematopoietic cells, and tissue-resident macrophages were derived from the injected AG-positive ESCs. We engrafted B6-derived tumor cells into the chimeras and identified tumor-infiltrating lymphocytes, tumor-associated macrophages, and VECs derived from donor cells. Moreover, tumor-infiltrating CD8+ T cells in these chimeric mice showed cytotoxic activity comparable to that in wild-type mice. We anticipate that this intraspecies chimeric mouse model can serve as a valuable tool for basic research. Furthermore, future humanized tumor models generated via blastocyst complementation have the potential to significantly advance anticancer drug development in the preclinical phase.